PENGARUH VIRTUAL REALITY MILLEALAB UNTUK MENINGKATKAN MINAT BELAJAR SISWA DI KELAS IV PADA MATA PELAJARAN KEWARGANEGARAAN - Mochamad Faridz; Dhea Adela (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of the Virtual Reality (VR) Millealab application on increasing the learning interest of fourth-grade students in Civics Education (PKn). A quantitative approach with a quasi-experimental method and a nonequivalent control group design was used, involving 30 fourth-grade students of SD Negeri 3 Nyalindung, divided into an experimental group (VR Millealab, n = 15) and a control group (conventional PowerPoint, n = 15). Learning interest was measured using a 22-item Likert questionnaire developed from Keller’s ARCS model and administered as a pretest and posttest. Data were analysed using JASP through descriptive statistics, the Shapiro-Wilk normality test, Levene’s homogeneity test, an independent samples t-test on N-Gain scores, and a supporting mixed ANOVA. The results showed that the pretest scores of both groups did not differ significantly (t = 0.57; p = .57), confirming baseline equivalence. After the treatment, the experimental group’s N-Gain (M = 0.57, medium category) was significantly higher than the control group’s (M = 0.25, low category), t(28) = 3.62, p = .001, Cohen’s d = 1.32, and this was reinforced by a significant Time × Group interaction in the mixed ANOVA, F(1, 28) = 6.48, p = .02. These findings indicate that VR Millealab has a significant effect on increasing students’ interest in learning Civics Education and can be considered as an innovative alternative instructional medium at the elementary school level.